Toward a new ultrasound-based imaging method for the diagnosis of acute pancreatitis: A preliminary study suggesting that it may be feasible - Şenateş, Ebubekir (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Şenateş E. Toward a new ultrasound-based imaging method for the diagnosis of acute pancreatitis: A preliminary study suggesting that it may be feasible. Turk J Gastroenterol 2018; 29: 256-8.